2018
DOI: 10.1016/j.jcat.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of the CO2 hydrogenation to fuels over Cu-Zr-SBA-15 catalysts

Abstract: The self-archived postprint version of this journal article is available at Linköping University Institutional Repository (DiVA): http://urn.kb.se/resolve?urn=urn:nbn:se:liu:diva-147297 N.B.: When citing this work, cite the original publication.Atakan, A., Erdtman, E., Mäkie, P., Ojamäe, L., Odén, M., (2018) ABSTRACT: Time evolution of catalytic CO2 hydrogenation to methanol and dimethyl ether (DME) has been investigated in a hightemperature high-pressure reaction chamber where products accumulate over time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Additionally, the bands at 1305, 1337, 1504, and 1543 cm −1 over CZA‐r are assigned to asymmetric and symmetric stretches of (OCO) of carboxylate species (*HOCO) . Furthermore, the bands at 2170 and 2120 cm −1 assigned to adsorbed CO species on Cu faces appear at 190 °C, and another band at 3010 cm −1 attributed to the ν (CH 4 ) appears at 230 °C . The band of methane at 3014 cm −1 appears at 260 °C over CZA‐r with a weaker peak intensity than that on CZA‐p (230 °C), suggesting suppressed CH 4 formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the bands at 1305, 1337, 1504, and 1543 cm −1 over CZA‐r are assigned to asymmetric and symmetric stretches of (OCO) of carboxylate species (*HOCO) . Furthermore, the bands at 2170 and 2120 cm −1 assigned to adsorbed CO species on Cu faces appear at 190 °C, and another band at 3010 cm −1 attributed to the ν (CH 4 ) appears at 230 °C . The band of methane at 3014 cm −1 appears at 260 °C over CZA‐r with a weaker peak intensity than that on CZA‐p (230 °C), suggesting suppressed CH 4 formation.…”
Section: Resultsmentioning
confidence: 99%
“…Figure and Figure S9 (in the Supporting Information) show the transient evolution of the surface species under reactive atmosphere from 150 to 300 °C over CZA‐p and CZA‐r, respectively. From Figure a and Figure S5 a (in the Supporting Information), the bands at 1054 and 2928 cm −1 assigned to the ν (C‐O) and ν (CH 3 ) modes of methoxy (*H 3 CO) appear at 170 °C over CZA‐p, whereas the bands appear at 160 °C on CZA‐r (Figure b and Figure S5 b in the Supporting Information). This indicates lower activation energy over CZA‐r for CO 2 hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the aforementioned hybrid catalysts, the supported bifunctional catalysts were also frequently used in the STD reactions . The supported catalyst can be produced by the coprecipitation, impregnation, sol‐gel, and wet‐chemical ways .…”
Section: Figurementioning
confidence: 99%
“…Recently, porous nanostructured materials as adsorbent of organic dyes have been one of the most extensively studied materials owing to its large surface and abundant active sites [9], of which SBA-15 materials as a typical representative representing suitable support exhibit wellaligned nanochannels, high surface area, large pore diameter and excellent thermal stability [10], with its modification by metal atoms, including Zr [11], Ti [12], Al [13], Fe [14], widely reported in the adsorption and catalytic fields, and particularly investigations to Ti-SBA-15 used for effective removal of organic dyes from a system attracting more attentions of reaesrchers [15]. Zhang and his group [16] prepared a series of Ti-containing SBA-15 samples in the self-generated acidic condition with catalytic tests indicating that Ti-SBA-15 showed much higher photodegradation ability towards RhB than pure TiO 2 and the work from Swapan K. Das et al [17] showed that synthesized Ti-SBA-15 with higher surface area than that of pure SBA-15, possessed larger H 2 uptake at higher external pressure and excellent efficiency in photocatalytic degradation of methylene blue, which indicate that the introduction of heteroatoms in SBA-15 materials is a promising approach to enhance the SBA-15 properties.…”
Section: Introductionmentioning
confidence: 99%